The persona lifecycle - Pruitt, John. (Elsevier,Morgan Kaufmann Publishers, an imprint of Elsevier, 2006)
"The Persona Lifecycle addresses the "how" of creating effective personas and using those personas to design products that people love. It doesn’t just describe the value of personas; it offers detailed techniques and tools related to planning, creating, communicating, and using personas to create great product designs. Moreover, it provides examples, samples, and illustrations to imitate and model. It positions personas not as a panacea, but as a method used to complement other user-centered design (UCD) techniques including scenario-based design, cognitive walkthroughs and user testing."--BOOK JACKET.